OAK AND FLOWERING DOGWOOD FRUIT PRODUCTION FOR EASTERN WILD TURKEYS - James G. Dickson (Wildlife Society Bulletin)
Abstract: Fruits of oak (Quercus spp.) and flowering dogwood (Cornus florida) are important foods for wild turkeys (Meleagris gallopavo silvestris) throughout eastern deciduous forests. To understand wild turkey ecology better and to manage forest habitat for wild turkeys, fruit production data for oaks and dogwood are needed. Annual fruit production was measured for 19 years in 4 hardwood habitat types in the Ozark Highlands of northern Arkansas. Mean annual acorn production ranged from 23 to 168 kg/ha, and mean annual dogwood fruit production ranged from 1.3 to 8.5 kg/ha for the habitat types. Annual production of acorns and flowering dogwood fruit was erratic in all stands. In each habitat type, acorn production was minimal (0‐22 kg/ha) in 5 of the 19 years and profuse in 9 years. The extreme year‐to‐year variation and minimal production of oak and flowering dogwood fruit some years point to the importance of managing for diverse wild turkey habitat with a diversity of food sources.